Antibacterial Activities of Calpurnia aurea against Selected Animal Pathogenic Bacterial Strains - Getachew Mulatu (Hindawi Limited, 2020)
The study aimed to determine the phytochemicals and to assess the antibacterial activities of crude extracts of different parts of Calpurnia aurea against Staphylococcus aureus, Streptococcus pyogenes, Listeria monocytogenes, Escherichia coli O157 H:7, Salmonella typhi, and Campylobacter jejuni. The fresh and healthy leaves, barks, stems, and roots of the plant parts were collected, herbarium, dried, and grounded, and bioactive compounds were extracted by ethanol (99%) and water. Mass of crude extracts was determined by using the Whatman No. 1 filter paper and rotary evaporator. Major secondary metabolites were also screened using phytochemical screening tests. Antibacterial activities (inhibition zones, mm) and minimum inhibition concentrations (MIC) were evaluated using agar-well diffused methods and agar dilution methods, respectively. The antibiotics ciprofloxacin, amoxicillin, penicillin, and tetracycline were used as positive controls at concentrations of 0.1 mg/ml and 0.2 mg/ml, while distilled water was used as the negative control. All the crude extracts were tested triplet (3x) for antibacterial activities against selected bacterial strains with two different concentrations 25 and 50 mg/ml and analyzed to compare the mean ± standard deviation between triplets. The results revealed that ethanol extracts showed high crude mass extracts, antibacterial activities, and major secondary metabolites such as alkaloids, tennis, flavonoids, saponins, steroids, and phlobatannins compared with aqueous extracts. Among antibiotics used, penicillin showed resistance to S. aureus and E. coli O157 H:7. C. jejuni was found to be the most susceptible bacterium to ethanol extracts' leaves, barks, and stems with MIC 3.125 mg/ml, whereas S. aureus was the least susceptible to all crude extracts. The study provided the traditional and scientific basis of Calpurnia aurea used against some bacterial diseases.